Association between sleep disturbances, fear of hypoglycemia and psychological well-being in adults with type 1 diabetes mellitus, data from cross-sectional VARDIA study. (February 2020) - Suteau, Valentine; Saulnier, Pierre-Jean; Wargny, Matthieu; Gonder-Frederick, Linda; Gand, Elise; Chaillous, Lucy; Allix, Ingrid; Dubois, Séverine; Bonnet, Fabrice; Leguerrier, Anne-Marie; Fradet, Gerard; Delcourt Crespin, Ingrid; et al.
Abstract: Aim: To assess the relationship between sleep quality, fear of hypoglycemia, glycemic variability and psychological well-being in type 1 diabetes mellitus. Methods: Our data were provided by the VARDIA Study, a multicentric cross-sectional study conducted between June and December 2015. Sleep characteristics were assessed by the Pittsburgh Sleep Quality Index (PSQI). Fear of hypoglycemia and psychological well-being were measured with the Hypoglycemia Fear Survey version II (HFS-II) and the Hospital Anxiety and Depression Scale (HADS), respectively. Glycemic variability (GV) was determined using the CV of three 7-point self-monitoring blood glucose profiles and the mean amplitude of glycemic excursion (MAGE). Results: 315 patients were eligible for PSQI questionnaire analysis: 54% women, mean age 47 ± 15, mean diabetes duration of 24 ± 13 years, HbA1c of 7.6 ± 0.9% (60 ± 7, 5mmol/mol). Average PSQI score was 6.0 ± 3.3 and 59.8% of the patients had a PSQI score > 5. HFS-II score and HADS were significantly higher among "poor" sleepers (p < 0.0001) and PSQI score was positively associated with HADS (β = 0.22; 95% CI = 0.08;0.35). GV evaluated by CV or MAGE did not differ between "poor" and "good" sleepers (p = 0.28 and 0.54, respectively). Conclusions: Adult patients with type 1 diabetes have sleep disturbances which correlate with psychological well-being. This study suggests that psychological management can be a target to improve sleep quality in adults with type 1 diabetes mellitus.